The Management of Wastewater Treatment Plants at Bhayangkara Hospital Kendari in 2022 - Tosepu, Ramadhan; Yulisti, Sry; Latoso, Rudi; ., Ice; ., Harleni (KnE Social Sciences, 2023)
There is efforts to manage wastewater and liquid waste, especially at the Bhayangkara Hospital Kendari, with various treatment processes to ensure it meets the requirements. The health of the hospital environment is essential. Therefore, proper and correct waste management efforts are needed so that its disposal complies with hospital wastewater quality standards requirements. Based on this, the researchers are interested in evaluating the management of the wastewater treatment plants at the Bhayangkara Hospital Kendari. This study aimed to evaluate the effectiveness of wastewater management and quality standards. The parameters of wastewater examined were temperature, TTS (Total Suspended Solids), pH (Degree of Similarity), NH3 (Ammonia), COD (Chemical Oxygen Demand), BOD (Biochemical Oxygen Demand), and Coliform MPN. The method used in this study was descriptive by collecting data through interviews and field observations to get an overview of the evaluation of wastewater treatment at the Bhayangkara Hospital Kendari, which would then be analyzed. The results of this study indicated that the effectiveness of treatment at the Bhayangkara Hospital Kendari had met the requirements according to Decree of the Minister of Health No. 1204/Menkes/SK/X/2004 regarding the process of treating wastewater using an Anaerobic-Aerobic Biofilter system and a chemical wastewater treatment system with an anaerobic-aerobic biofilter system to produce effluent according to quality standards. The measurement results for each waste parameter were by the Decree of the Minister of Environment No. 5 of 2014 concerning hospital wastewater quality standards, namely the temperature value at the outlet (after processing) was 28, TDS at the outlet was 170 mg/L, TSS at the outlet was 45 mg /L, PH at the outlet was 7.89 mg/L, Free NH3 at the outlet was 0.057 mg/L, COD at the outlet was 15.70 mg/L, BOD at the outlet was 3.9 mg/L, and fatty oil at the outlet was <0.002 mg/L. Therefore, Bhayangkara Hospital Kendari already had quality standards and was suitable for disposal into the nearest canal. Keywords: Wastewater, Quality Standards, Management of Wastewater Treatment Plants, Bhayangkara Hospital Kendari